Judicial Review “Satu Atap” Peraturan Perundang-Undangan di Bawah Kewenangan Mahkamah Konstitusi - Yunaldi, Wendra (Universitas Muhammadiyah Sumatera Barat, 2018)
The constitutional dual judicial review of the Constitutional Court and the regulation in the Supreme Court has created legal uncertainty in the legal system of Indonesia. The application of graded judicial review has a negative impact on the guarantee of the constitutional rights of the community. The hierarchical model of the prevailing law-enforcement regulation is the abandonment of the legal norms of the constitution in every level of legal product downward. Disconnection of constitutional norms only up to the level of the Act will be a denial of the rights of the people of Indonesia at all levels of statutory legislation under the law. As a rule of law, legal products have a value of truth and justice that refers to the source of the main legal order, namely the Constitution, so that Indonesia's constitutionalism can be tiered up and down down. Thus, there is no differentiation of the